Dynamics of structural change and the quality of institutions in the context of an open developing economy - (:unkn) unknown (My University, 2024)
"Institutions are the man-made constraints that structure political, economic and social interactions." North (1991). According to Levchenko (2007), the term "institutions" refers to a wide range of structures that influence economic outcomes such as contract enforcement, property law, etc... Referring to the literature on institutions, it indicates that institutions play an important role in economic performance. In terms of structural change, different patterns of structural change have been observed in both formerly and newly industrialized countries. Given the importance attached to institutions in recent economic studies, the question was posed intuitively in order to understand the role of institutions in these different models of structural change.Chapter 1 examines the relationship between institutional quality and structural change. We look at which types of institutions (political, legal and economic) are most important in the process of structural change, over a sample of 103 countries from 1984 to 2018. We first use the technique of principal component analysis and hierarchical ascending classification to explore our dataset. Then, we empirically investigate the relationship using a threshold panel model. We find that legal, economic and political institutions have significant effects on structural change. However, these effects differ according to the level of institutional thresholds.When considering international integration in chapter 2, it is generally viewed in terms of its impact on a country's growth and/or development. We examine the relationship between openness and structural change, with the notion of institutional threshold over a sample of 98 countries between 1984 and 2018 and using GMM system. Our study shows that institutional quality is important in explaining the relationship between openness and structural change. However, its importance is only relevant when countries reach a certain threshold of institutional quality.
Keywords: African Research